2004
DOI: 10.1124/dmd.104.001347
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Cytochromes P450 in Chimeric Mice With Humanized Liver

Abstract: ABSTRACT:Recently, a chimeric mouse line in which the liver could be replaced by more than 80% with human hepatocytes was established in Japan. Because the chimeric mouse produces human albumin (hAlb), replacement by human hepatocytes could be estimated by the hAlb concentration in the blood of chimeric mice. In this study, we investigated human major cytochrome P450 (P450) in the livers of chimeric mice by mRNA, protein, and enzyme activity using real-time polymerase chain reaction, Western blot analysis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 32 publications
3
80
1
1
Order By: Relevance
“…Many recent publications have unambiguously demonstrated the value of humanized mouse livers for the study of drug metabolism and hepatitis research [7][8][9]21,[23][24][25][26][27][28][29] . However, the albumin-uPA transgenic mouse used for these studies has several major practical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent publications have unambiguously demonstrated the value of humanized mouse livers for the study of drug metabolism and hepatitis research [7][8][9]21,[23][24][25][26][27][28][29] . However, the albumin-uPA transgenic mouse used for these studies has several major practical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxylation at the 49-position is one of the major metabolic routes of dmd.aspetjournals.org diclofenac, and metabolite II has been used as a marker of human CYP2C9 activity in humanized animal models. The in vitro assessment using liver microsome preparations from humanized uPA/severe combined immunodeficient chimeric mice with varying replacement ratios showed that the formation of II correlated well with hepatic replacement ratio, relative expression levels of CYP2C9 mRNA, and CYP2C9 protein content (Katoh et al, 2004;Tateno et al, 2004). Recently, Hu et al (2013) produced humanized TK-NOG chimeric mice using hepatocytes from donors with different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The diclofenac 4Ј-hydroxylase activity was determined by the method used by Katoh et al (2004) with a 30-min incubation time. The product formation was determined using HPLC with a TSK-GEL ODS-80T M column (4.6 ϫ 250 mm; 5 m; TOSOH, Tokyo, Japan) and monitored at 280 nm.…”
Section: Methodsmentioning
confidence: 99%